(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Over the past two decades, Friuli-Venezia Giulia has been the scene of emblematic cases of end-of-life and self-determination, which have profoundly impacted Italy’s ethical and institutional debate. From the Englaro case to the most recent experiences of medically assisted suicide, the Region has developed an original ethical-organizational model, based on the Ethics Units for Clinical Practice (NEPC) and the Regional Single Ethics Committee (CEUR). The paper traces the historical and normative stages of this journey, highlighting how NEPCs have assumed a central role in supporting complex clinical decisions, preventing conflict, and promoting a culture of discussion, listening, and shared responsibility in end-of-life decisions.